Wildlife impacts and vulnerable livelihoods in a transfrontier conservation landscape. Issue 4 (14th May 2020) - Salerno, Jonathan; Bailey, Karen; Gaughan, Andrea E.; Stevens, Forrest R.; Hilton, Tom; Cassidy, Lin; Drake, Michael D.; Pricope, Narcisa G.; Hartter, Joel
Abstract: Interactions between humans and wildlife resulting in negative impacts are among the most pressing conservation challenges globally. In regions of smallholder livestock and crop production, interactions with wildlife can compromise human well‐being and motivate negative sentiment and retaliation toward wildlife, undermining conservation goals. Although impacts may be unavoidable when human and wildlife land use overlap, scant large‐scale human data exist quantifying the direct costs of wildlife to livelihoods. In a landscape of global importance for wildlife conservation in southern Africa, we quantified costs for people living with wildlife through a fundamental measure of human well‐being, food security, and we tested whether existing livelihood strategies buffer certain households against crop depredation by wildlife, predominantly elephants. To do this, we estimated Bayesian multilevel statistical models based on multicounty household data ( n = 711) and interpreted model results in the context of spatial data from participatory land‐use mapping. Reported crop depredation by wildlife was widespread. Over half of the sample households were affected and household food security was reduced significantly (odds ratio 0.37 [0.22, 0.63]). The most food insecure households relied on gathered food sources and welfare programs. In the event of crop depredation by wildlife, these 2 livelihood sources buffered or reduced harmful effects of depredation. The presence of buffering strategies suggests a targeted compensation strategy could benefit the region's most vulnerable people. Such strategies should be combined with dynamic and spatially explicit land‐use planning that may reduce the frequency of negative human–wildlife impacts. Quantifying and mitigating the human costs from wildlife are necessary steps in working toward human–wildlife coexistence. Abstract : Article Impact statement : Multicounty household data show livelihood costs from wildlife crop depredation. Abstract : Impactos de la Fauna y Medios de Subsistencia Vulnerables en unkl Paisaje de Conservación Transfronteriza Resumen: Las interacciones entre los humanos y la fauna que resultan en impactos negativos se encuentran entre los desafíos más apremiantes para la conservación a nivel mundial. En las regiones de ganaderos y agricultores minifundistas, las interacciones con la fauna pueden poner en peligro el bienestar humano y motivar sentimientos negativos y represalias hacia la fauna, lo que debilita los objetivos de conservación. Aunque los impactos pueden evitarse cuando el uso de suelo por humanos y fauna se traslapa, existen pocos datos humanos a gran escala que cuantifiquen el costo directo de la fauna para los medios de subsistencia. Cuantificamos el costo para las personas que conviven con animales silvestres en un paisaje de importancia global para la conservación de fauna en el sur de África. La cuantificación fue realizada por medio de una medida fundamental de bienestar humano y seguridad alimentaria, y probamos si las estrategias existentes de subsistencia amortiguan a ciertos hogares ante la depredación de cultivos realizada por animales silvestres, predominantemente los elefantes. Para realizar esto, estimamos algunos modelos estadísticos bayesianos de niveles múltiples basados en los datos de hogares ubicados en múltiples condados ( n  = 711) e interpretamos los resultados de los modelos en el contexto de los datos espaciales a partir de un mapeo participativo de uso de suelo. La depredación de cultivos por animales silvestres fue reportada de manera generalizada. Más de la mitad de los hogares en la muestra estuvieron afectados y la seguridad alimenticia de los hogares se redujo significativamente (proporción de probabilidades 0.37 [0.22, 0.63]). Los hogares con la menor seguridad alimentaria dependían de fuentes de recolección de alimentos y programas de bienestar. En el evento de la depredación por fauna de los cultivos, estas dos fuentes de subsistencia amortiguaron o redujeron los efectos dañinos de la depredación. La presencia de las estrategias de amortiguamiento sugiere que una estrategia de compensación enfocada podría beneficiar a las personas más vulnerables de la región. Dichas estrategias deberían estar combinadas con la planeación del uso de suelo dinámica y espacialmente explícita, la cual podría reducir la frecuencia de los impactos negativos entre los humanos y la fauna. La cuantificación y mitificación del costo humano a partir de la fauna son pasos necesarios en el camino hacia la coexistencia entre los humanos y la fauna. 摘要: 人类与野生动物之间相互作用造成的负面影响是全球最紧迫的保护挑战之一。在小农畜牧和作物种植地区, 与野生动物的相互作用可能损害人类福祉, 并引发人类对野生动物的负面情绪和报复行为, 进而破坏保护目标。人类和野生动物在土地利用重叠时难免产生相应影响, 但在量化野生动物对人类生计的直接影响成本时仍缺乏大尺度的人类数据。我们在南非一个具有全球重要意义的野生动物保护的景观中, 利用人类福祉和粮食安全的基本指标定量分析了人类与野生动物一起生活的成本, 我们还分析了现有生计策略在防止野生动物 (主要是大象) 掠夺农作物中是否能对一些家庭起到缓冲作用。我们基于多个国家的家庭数据 ( n = 711) 进行了贝叶斯多层统计模型估计, 并结合参与式土地利用绘图的空间数据对模型结果做出解释。结果发现, 野生动物对农作物的破坏非常普遍, 样本中一半以上的家庭都受到了影响, 这导致粮食安全显著下降 (优势比为 0.37 [0.22, 0.63]) 。而最缺乏粮食安全保障的家庭主要依赖于收集的食物和福利计划维持生计。当作物遭到野生动物的破坏时, 这两种生计来源可以缓冲或减少破坏的有害影响。缓冲策略的存在表明, 有针对性的补偿策略可以帮助该地区最弱势的群体。而这些策略应与动态及空间显式土地利用规划相结合, 以减少人类‐野生动物负面影响发生的频率。因此, 量化和减少野生动物对人类造成的损失是努力实现人类与野生动物共存的必要步骤。【翻译: 胡怡思; 审校: 聂永刚】